Mitogen‐activated Tasmanian devil blood mononuclear cells kill devil facial tumour disease cells. Issue 7 (24th May 2016) - Brown, Gabriella K; Tovar, Cesar; Cooray, Anne A; Kreiss, Alexandre; Darby, Jocelyn; Murphy, James M; Corcoran, Lynn M; Bettiol, Silvana S; Lyons, A Bruce; Woods, Gregory M
Abstract : Devil facial tumour disease (DFTD) is a transmissible cancer that has brought the host species, the Tasmanian devil, to the brink of extinction. The cancer cells avoid allogeneic immune recognition by downregulating cell surface major histocompatibility complex (MHC) I expression. This should prevent CD8 + T cell, but not natural killer (NK) cell, cytotoxicity. The reason why NK cells, normally reactive to MHC‐negative cells, are not activated to kill DFTD cells has not been determined. The immune response of wild devils to DFTD, if it occurs, is uncharacterised. To investigate this, we tested 12 wild devils with DFTD, and found suggestive evidence of low levels of antibodies against DFTD cells in one devil. Eight of these devils were also analysed for cytotoxicity, however, none showed evidence for cytotoxicity against cultured DFTD cells. To establish whether mimicking activation of antitumour responses could induce cytotoxic activity against DFTD, Tasmanian devil peripheral blood mononuclear cells (PBMCs) were treated with either the mitogen Concanavalin A, the Toll‐like receptor agonist polyinosinic:polycytidylic acid or recombinant Tasmanian devil IL‐2. All induced the PBMC cells to kill cultured DFTD cells, suggesting that activation does not occur after encounter with DFTD cells in vivo, but can be induced. The identification of agents that activate cytotoxicity against DFTD target cells is critical for developing strategies to protect against DFTD. Such agents could function as adjuvants to induce functional immune responses capable of targeting DFTD cells and tumours in vivo .